2019
DOI: 10.5546/aap.2019.349
|View full text |Cite
|
Sign up to set email alerts
|

Pantallas: discordancias entre las recomendaciones y el uso real

Abstract: La utilización de dispositivos electrónicos con pantallas y su introducción cada vez más temprana en la vida de los niños presentan un desafío que debe ser reconocido por el pediatra para contribuir a evitar su exceso. Se ha detectado una manifiesta discordancia entre las recomendaciones ideales y el uso real de las pantallas en los niños pequeños. Un correcto asesoramiento dentro de un contexto familiar, junto con una evidencia más sólida sobre los impactos a largo plazo del uso de la tecnología digital, perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
2
2
0
3
Order By: Relevance
“…Regarding the rest of the media, on average, toddlers used them for less than an hour per day and most of the toddlers hardly used the Tablet and PC. Our results were similar to other studies (Cristia & Seidl, 2015 ; Tabullo & Gago-Galvagno, 2022 ; Simaes et al, 2022 ) that show that in this age range the usage of digital media is low, but it is more than the pediatrics associations’ zero screen recommendation for this age group (Melamud and Waisman 2019 ; Sas & Estrada, 2021 ; Schwarzer et al, 2021 ), and there is a tendency for screen use to increase in this population with age (Cristia & Seidl, 2015 ; Schwarzer et al, 2021 ). It is interesting to note that when media was used by toddlers, parents often shared in this activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the rest of the media, on average, toddlers used them for less than an hour per day and most of the toddlers hardly used the Tablet and PC. Our results were similar to other studies (Cristia & Seidl, 2015 ; Tabullo & Gago-Galvagno, 2022 ; Simaes et al, 2022 ) that show that in this age range the usage of digital media is low, but it is more than the pediatrics associations’ zero screen recommendation for this age group (Melamud and Waisman 2019 ; Sas & Estrada, 2021 ; Schwarzer et al, 2021 ), and there is a tendency for screen use to increase in this population with age (Cristia & Seidl, 2015 ; Schwarzer et al, 2021 ). It is interesting to note that when media was used by toddlers, parents often shared in this activity.…”
Section: Discussionsupporting
confidence: 92%
“…In this case, being such young toddlers, the associations could be negative because the content used on this type of device is not age-appropriate (Madigan et al, 2020 ; Sas & Estrada, 2021 ). However, it is necessary to highlight that the effect of PC on vocabulary was also observed after controlling for sociodemographic variables in the regression models, which reinforces the findings of other studies (Madigan et al, 2020 ; Medawar et al, 2023 ) and recommendations from pediatric societies to moderate consumption in early childhood (Melamud and Waisman 2019 ; Sas & Estrada, 2021 ; Schwarzer et al, 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the use of screens, it has been observed that excessive use beyond the recommendations is related to a sedentary lifestyle and a decrease in physical exercise during leisure time [19,40]. This may increase the risk of becoming overweight or obese, and it may negatively influence academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the possibility of receiving commercial advertising or exposure to violent or pornographic content. By participating in the networks without any type of supervision, they can provide inappropriate information, be subjected to grooming or harassment and, in turn, can be actors of these same actions (Melamuda & Waismanb, 2019).…”
Section: Use Of Screens and Associations With Language And Motor Skillsmentioning
confidence: 99%